Asymmetric ionic aerogel of biologic nanofibrils for harvesting electricity from moisture. (May 2020) - Yang, Weiqing; Li, Xiankai; Han, Xiao; Zhang, Weihua; Wang, Zengbin; Ma, Xiaomei; Li, Mingjie; Li, Chaoxu
Abstract: Artificial asymmetric ionic membranes have attracted great interests in harvesting electricity from ubiquitous water activities, while mostly based on delicately-designed nanopores/nanochannels, either to harness saline water in mimic of cytomembranes or to harness moisture with carbon nanomaterials. Herein, fully biological asymmetric ionic aerogels were fabricated from biological oppositely-charged nanofibrils through a facile freeze-casting method. When exposing to moisture, these nanofibrils may be hydrated by capturing moisture and thus simulate the charged nanochannels for ion transport. Ion dissociation and diffusion ions would induce directional movement of charges, thereby leading to a potential up to 115 mV. With sustainability, biocompatibility and biodegradability, these biological nanogenerators may promise a low-cost and high-efficiency electricity harvest strategy from moist air, being capable of serving as self-powered wearable, biomedical and miniaturized electronic devices. Graphical abstract: Asymmetric ionic aerogel of biologic nanofibrils can capture air moisture to form ion conductive networks with hydrated nanochannels, and diffusion and neutralization of the dissociated positive and negative ions could induce directional movement of charges, thereby leading to a potential. These biological moisture nanogenerators promise a low-cost and high-efficiency electricity harvest strategy, capable of serving as self-powered wearable, biomedical and miniaturized electronic devices. Image 1 Highlights: Asymmetric ionic aerogels of biological nanofibrils fabricated via freeze-casting. The aerogels capture air moisture to form hydrated and ion conductive networks. Ion dissociation and diffusion ions leading to a potential up to 115 mV. A biological moisture-energy harvesting strategy for self-powered wearable devices.